Design specification development on eco-design chair through users’s perception analysis and Kansei Engineering evaluation - Rusli, Asa Naim (2018)
The approach of eco-design has gained wide attention globally as an alternative method to reduce harm to the environment. This approach is seen as providing a sustainable solution that integrates human needs and at the same time reduces environmental burden. Studies on various eco-design aspects have been carried out with regard to environmental engineering approaches, emphasising on waste management, pollution control and production site cleaning and disposal which are usually conducted at the end of the processing stage. Consequently, changes to eco-design products are difficult to be perceived and appreciated by users. As such, a study on users' perceptions towards eco-design products has been suggested in early stage of design development process as an alternative to reduce environmental loads. Unfortunately, the perception of product value based on appearance is often intuitive and emotional, and it is difficult to quantify. With this gap as a constraint, the study focuses on the eco-design of a chair as seating is often related to emotional aspects; thus, and enables to fulfil the needs of eco design requirements. The goal of this study was to determine the relationship between users’ perceptions and eco-design attributes in improving design specifications as an alternative to increase consciousness in reducing environmental burden. Kansei Engineering (K.E.) methodology was applied and the Satellite Terminal Building, KLIA was chosen as the study area. Phase I of the study involved the decision of strategy attempted to support the demonstrable facts and provided answer to the research question and the resolution to the problem. Phase II of the study (Part A and Part B) was conducted to achieve these purposes: firstly, to identify the perception on the existing airport chair corresponding to the environmental consciousness in KLIA; and secondly, to identify the elements of desirable eco-design attributes that reflect environmental consciousness in KLIA. Phase III involved the detailed stages of Kansei experiments which comprised the collection and construction of Kansei’s instrument tools, and Kansei evaluation experiment. In addition, this phase verified sitting comfort using the Force Sensitive Application (FSA). The findings of the study revealed the requirements needed to achieve an effective design specification for eco-design chair from the users’ perspective which demanded the application of several requirements. Phase I introduced Kansei Words which represent emotional impressions towards the attributes of an eco-design chair. The selected Kansei Words were finalised into Kansei Affinity Cluster, in accordance to the priorities of subjective and qualitative data in eco-design attributes. The findings of Phase II (Part A) revealed that the external appearance of an eco-design chair should be attractive, had a natural look with a green colour scheme and made of recycled materials. Users’ high perception of the value of recyclable materials were found to be based on the state of the art of the design of the chair, and they felt that the versatility of recycled materials with variety of textures and patterns were able to reflect the environmental consciousness in KLIA. This was in contrast to the findings of Phase II (Part B) which revealed that the existing airport chairs had been perceived as having a simple design with a dark and dull colour scheme; thus, they failed to reflect environmental consciousness in KLIA. In addition, the study found that users were not able to judge on the types of materials used and component parts in the existing airport chairs as the materials used were clearly not made from natural materials. Nevertheless, the findings revealed that the whole components of existing airport chairs did fulfil the ergonomic requirements even though they did not provide maximum comfort for users to sit longer. With regard to aesthetic aspect, it was revealed that users desired eco-design attributes that used eco-materials in geometrics form with modern and simple design and used green natural colours to reflect KLIA as an environmentally friendly airport. Besides that, the study found that ergonomic aspects were perceived as the main requirement in providing comfort and helping users to refresh their body before they continue their journey. As a conclusion, findings of both Part A and Part B in Phase II showed that although the surficial aesthetics on eco-design attributes were capable of portraying environmental consciousness in KLIA, ergonomic attributes remained important. As good ergonomics was viewed as a pre-condition for comfort, Phase III highlighted the emotional eco-design chair that integrated both ergonomics and aesthetic aspects through detailed stages of Kansei evaluation experiments. The findings of Phase III revealed that to fulfil the requirements of ergonomic aspect in the design, shape and form with regard to the depth, width and height of seats and backrest chair were the significant factors that needed to be emphasised in design specifications. The use of curve foam padding in certain parts of both the seats and backrests chair were viewed as essential in determining design specifications. Through the validation among designers, this study demonstrates that guidelines on eco-design chair is beneficial to designers and users. The furniture designers involved agrees that this guideline is generic enough to be understood by non-designers and non-technical background of users. Although the study was performed with limitations and constraints, the findings provided several novel foundations in the engineering of emotion in the development of a guideline in eco-design chairs.